2011
DOI: 10.1002/ange.201103074
|View full text |Cite
|
Sign up to set email alerts
|

Lewis‐Säure‐vermittelte benzylische Kreuzkupplungen von Pyridinen mit Arylbromiden

Abstract: ZnCl2, Sc(OTf)3 oder BF3⋅OEt2 vermitteln die Pd‐katalysierte Arylierung von Methylpyridinen und ähnlichen Heterocyclen (siehe Beispiel). Die Komplexierung des Stickstoffatoms im Heterocyclus durch die Lewis‐Säure erleichtert die reduktive Eliminierung, was in hohen Ausbeuten zu zahlreichen arylierten Produkten führt. Mit BF3⋅OEt2 gelingt darüber hinaus im Fall des 2,4‐Lutidins eine hoch regioselektive Metallierung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…For example, the groups of Hartwig3a and Nolan3b have reported that Lewis acids such as AlCl 3 and BEt 3 accelerate palladium‐mediated reductive elimination reactions. Knochel reported the direct palladium‐catalyzed arylation of methyl‐substituted pyridine promoted by ZnCl 2 , Sc(OTf) 3 , and BF 3 ⋅ OEt 2 with excellent regioselectivity 3c. Similarly, our group,4 as well as those of Nakao and Hiyama5 and Kanai,6 have observed the beneficial effect of added AlMe 3 in promoting nickel‐mediated CH bond activation of heteroarenes.…”
Section: Introductionsupporting
confidence: 59%
“…For example, the groups of Hartwig3a and Nolan3b have reported that Lewis acids such as AlCl 3 and BEt 3 accelerate palladium‐mediated reductive elimination reactions. Knochel reported the direct palladium‐catalyzed arylation of methyl‐substituted pyridine promoted by ZnCl 2 , Sc(OTf) 3 , and BF 3 ⋅ OEt 2 with excellent regioselectivity 3c. Similarly, our group,4 as well as those of Nakao and Hiyama5 and Kanai,6 have observed the beneficial effect of added AlMe 3 in promoting nickel‐mediated CH bond activation of heteroarenes.…”
Section: Introductionsupporting
confidence: 59%
“…In the case of cyano-substituted aryl bromides (5b and 5j), we have found that the addition of 10% Sc(OTf) 3 17 improves the cross-coupling yield. 5,18 The generality of our approach is demonstrated by performing the arylation of other related 5-membered heterocycles such as the 2-methylindole derivative 14 19 and the 2-methylbenzimidazole 15. 20 In these cases, TMPZnCl 3 LiCl (1) proved to be a suitable base, and a complete zincation could be obtained within 1 h at 25 °C.…”
mentioning
confidence: 99%
“…m.p 145-147 8C. 1 H NMR, 13 Single-crystal X-ray Structure Determination [8] Crystals were each mounted on a glass capillary in perfluorinated oil and measured in a cold N 2 flow. The data were collected on an Oxford Diffraction Xcalibur S Sapphire at 150(2) K (Mo Ka radiation, l = 0.71073 ).…”
Section: Synthesis Of 2 Bmentioning
confidence: 99%